The Register of the Lynn Historical Society. - Lynn Historical Society (Lynn, Mass.) (Tufts University. Tisch Library., 2016)
1 online resource : ill.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.